Innovation strategies and productivity in the Polish services sector in the light of CIS 2008 - Krzysztof Szczygielski; Wojciech Grabowski (Center for Social and Economic Research (CASE), 2012)
Industry - and firm-level research into both innovations and productivity has long been limited to manufacturing. With this paper, we aim to contribute to the stream of literature that aims at extending the scope of such investigations to the services industry. To this end we analyze the innovation strategies in several service sectors in Poland in 2008 and examine their relationship to productivity. Our results show that service firms differ considerably in their innovation strategies, but that most of those strategies lead to productivity gains.
Keywords: L80; O31; L25; 330; services; service innovation; innovation strategy; firm productivity; Innovationsmanagement; Produktivität; Dienstleistungssektor; Polen